Stakeholders co-design workshop on cattle, tilapia, feeds, forages and water management- Lusaka, Zambia - Mwendia, Solomon; Mapedza, Everisto D. (2025)
The Sustainable Animal and Aquatic Foods (SAAF) program is one of eight CGIAR science programs operating in selected countries across Latin America, Africa, and Asia. Launched in 2025 and scheduled to run through 2030, SAAF builds upon earlier CGIAR initiatives that concluded in 2024. While Zambia participated in these prior initiatives, its livestock sector was not included. SAAF now brings this focus to the southern African region. The program is designed to collaborate with other CGIAR Science Programs, such as working with the Breeding for Tomorrow program on forages in Zambia.